Automated Lathe Machine - Hairul Mubarak,; Othman, Abdullah Ariff Ariffin; Azman, Muhammad Akmal Hanif; Supaat, Muhammad Fadhil; Basharie , Siti Mariam; Othman, Khairulnizam (Multidisciplinary Applied Research and Innovation, 2020)
Wood craft is one of the many hand crafts that exist in this country. Wood craft can be done in various way especially turning. Since there is always demands from tourists, wood craft industries required precise, accuracy, speed and consistency in its production. One of most popular mechanical equipment, CNC (Computer Numerical Control) machine. However, it is hard to afford CNC machine since it is expensive and too big to be stored in their workshop. Many of woodcrafter still using conventional method which done manually with high specific skill. This method is difficult, takes times and impossible to be done by non-skilled person. Based on the problem, the idea is to replicate conventional lathe machine into an automated one which works exactly like CNC machine. This machine built in a small size and cost much cheaper than market’s CNC machine. The 2-axis machine will be controlled by Arduino Uno which has been interfaced with Grbl firmware. Autodesk Fusion 360 is used to design the required shape of handicraft and save it in G-code. Arduino Uno will receive and process G-code and send it to motor driver to translates it into axial motion according to point coordinates. After testing, the replicated automated lathe machine can move nearly accurate and can be works on wood with maximum length of 100mm.